2014
DOI: 10.1021/ac500439m
|View full text |Cite
|
Sign up to set email alerts
|

Improved Separate Solution Method for Determination of Low Selectivity Coefficients

Abstract: Simple, fast, and theoretically substantiated experimental method for determination of improved selectivity coefficients is proposed. The method is based on the well-known fact that low selectivity coefficients determined by the separate solution method (SSM) are time-dependent and, upon our finding, this dependence is a well-defined linear function of time raised to the certain negative power. In particular, the selectivity coefficients obtained for equally charged primary and foreign ions by SSM linearly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The estimated values of the selectivity coefficients K A,B pot lim , in contrast to ones experimentally obtained by SSM, are practically independent of the concentration level of the foreign ion and are very close to unbiased values obtained by Bakker’s method 14. It should be noticed that the proposed method is even more effective in comparison with the one described in 29, as it never gives absurd results.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The estimated values of the selectivity coefficients K A,B pot lim , in contrast to ones experimentally obtained by SSM, are practically independent of the concentration level of the foreign ion and are very close to unbiased values obtained by Bakker’s method 14. It should be noticed that the proposed method is even more effective in comparison with the one described in 29, as it never gives absurd results.…”
Section: Resultssupporting
confidence: 76%
“…For very low K A,B pot lim values the inaccuracy in its determination can exceed 100 % leading to absurd negative values. It was experimentally found that the lowest selectivity coefficients, which can be determined by this method, are about n×10 −7 29.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For many years that parameter, however, was not uniformly determined as diverse protocols and methods were applied, many of which resulted in the determination of biased selectivity coefficient. In order to compare and verify different ionophores, currently there is a requirement for reporting unbiased selectivity coefficients [6,7]. Therefore, a common methodology, the separate solution method (SSM) and the fixed interference method (FIM) for ISEs selectivity determination were adapted [5,8].…”
Section: Page 3 Of 18mentioning
confidence: 99%
“…Several approaches have been reported in the literature to solve this problem, including the so‐called modified separate solution method (MSSM) [7c], which is based on preconditioning the membrane with a discriminated ion instead of the analyte ion, and the extrapolation of the time‐dependent electrode responses in a solution of interfering ions [7d,e]. An obvious limitation of the first method is that it can no longer be used after first contact with primary ions.…”
Section: Introductionmentioning
confidence: 99%